On maximum signless Laplacian Estrada index of graphs with given parameters - Ellahi, Hamid Reza (Ars mathematica contemporanea, 2016)
For a simple graph ?$G$? on n vertices, the signless Laplacian Estrada index is defined as ?$SLEE(G) = \sum_{i=1}^n e^{q_i}$ where $q_1, q_2, … , q_n$? are the eigenvalues of the signless Laplacian matrix of ?$G$?. In this paper, the unique graph on ?$n$? vertices with maximum signless Laplacian Estrada index is determined among graphs with given number of cut edges, pendent vertices, (vertex) connectivity and edge connectivity, respectively.
Keywords: cut edge; edge connectivity; nepredznačeni laplaceovski Estrada index; pol-povezavni sprehod; povezavna povezanost; prerezna povezava; semi-edge walk; signless Laplacian Estrada index; vertex connectivity; vozliščna povezanost